Sexuality, gender and schooling : shifting agendas in social learning - Kehily, Mary Jane (RoutledgeFalmer, 2002)
The sexuality of young people arouses controversy and remains a source of concern for parents, teachers, policy-makers and politicians. But what young people really think about sexuality and gender and how these issues impact upon their lives is often marginalized or overlooked. Based upon extensive ethnographic research with young people and teachers, Sexuality, Gender and Schooling offers a telling and insightful account of how young people acquire sexual knowledge and how they enact their understanding of their own gender. It highlights the ways in which young people's constructions of gende.